The Development of Web-Based Learning Media (Glideapps) to Improve Digital Literacy and Science Literacy About Materials Human Digestive Systems - Charolin Aprilia; Evita Anggereini; Nazarudin Nazarudin; Yuni Ahda (Jurnal Penelitian Pendidikan IPA, 2023)
Learning media is part of learning that contains messages, people, and devices, which follow technological developments. This study aims to determine the feasibility of developing web-based learning media to improve digital and scientific literacy skills in the material of the human digestive system in class VIII J at SMP Negeri 11 Jambi City. This research development uses the Dick & Carey development model. The test subjects consisted of a small group of 6 people and a large group consisting of 33 students who were students of Junior High School state 11 Jambi. The instruments used in this study were interviews, questionnaires, tests, and validation assessment sheets. This study uses a one-shot case study experimental design. The data analysis technique used in this research is descriptive research with a quantitative approach. The results of this study are media validation. The first material validation gets a score of 56%, and the classification of eligibility is not good, with several improvements. The second gets a score of 72%, the classification of eligibility is good, and the third gets a score of 91%, the classification is very good. The first media validation gets a score of 50%, and the feasibility classification is not good, with several improvements. The second gets a score of 72%, the feasibility classification is good, and the third gets a score of 94%, and the classification is very good. The effectiveness of web-based learning media (glideapps) in increasing digital literacy was carried out in large group tests obtaining an average value of 0.7757 or 77.5712% with high category in effective interpretation. The effectiveness of web-based learning media (glideapps) in increasing sains literacy is carried out in large group tests obtaining an average value of 0.7836 or 78.3601 % with high category in effective interpretation.